Optimization Of Diebond And Wirebond To Improve Non Stick On Pad Issue - Musa, Khaliza (2020)
One of the largest losses in semiconductor assembly operations is non-stick on pad (NSOP) failures. NSOP failures are costly as the entire device will need to be rejected if there is one such failure on any bond pad. The review is aim to look at the failure modes associated with poor bond pad quality, its causes, effects, and how the parameter changed can reduce the NSOP. For a assembly process, the earlier the defect was diagnosed, the easier and cheaper is the rectification of the defect. Therefore, the purpose of prevention or early detection is to produce a product with zero or minimal defects. Reducing the NSOP rate is the main target of this project parallel with company target to achieve Zero Defect target. Evaluating the reliability factor is one of the practical method to be used in order to reduce NSOP rate. Eight Design of Experiment (DoE) will be carried out and the data will be out and analyzed using JMP software. The experiment in this study prove that optimization of process parameter in wirebond and die bond process can solve the NSOP issue. Along reliability activity, it was proved that NSOP topic also relate to the lifted ball bond failure Therefore, the output response for this study are ball pull, ball shear and NSOP rate for every samples will be used for bondability assessment and the raw data will be plotted and analyzed accordingly. Requirement of sample size will be compliance as AEC QIOO standard. From this research, the optimum parameter to have a good bonding strength for is a combination of high power, high force and thinner BLT for the new technology using material nickel based bond pad for front side metallization, Ablebond glue type and copper wire.